RESTRICTIONS TO THE PRINCIPLE OF OPENNESS IN POLISH CIVIL PROCEEDINGS - Zembrzuski, Tadeusz (Zbornik radova Pravnog fakulteta u Nišu, 2024)
The principle of openness, considered one of the fundamental procedural rules, is deeply rooted in Polish law. It is considered a basic safeguard of securing proper and impartial justice, and due access to the judiciary. It has been legitimated under Article 45 clause 1 of the Constitution of the Republic of Poland, pursuant to which everyone has the right to a fair and public hearing without undue delay by a competent, independent, impartial and independent court of law. The mechanism is reflected in systemic legal provisions regarding the organisation of justice, as well as in the Code of Civil Procedure. While the nature of the principle of openness is not absolute, it has been formally and universally accepted that the rule shall be subjected to no restrictions in judicial proceedings. Contrary to the above, changes to Polish procedural law over the years have resulted in a condition wherein the exception has become a de facto rule. Contemporarily, there are options of adjudicating with the openness principle set aside not only with regard to formal or procedural matters, but merits of the case as well.The article is intended to present the evolution of the principle of openness in judicial proceedings in Poland, as something akin to a warning to other states against the risk of undermining the essence of that principle despite the formal preservation of the standard in question on systemic and statutory levels alike.
Keywords: начела судског поступка; начело јавности поступка; затворене седнице; интерна и екстерна транспарентност; ограничења начела јавности поступка